On the long term storage of forensic DNA in water. (December 2019) - Zupanič Pajnič, Irena; Marrubini, Giorgio; Pogorelc, Barbara Gornjak; Zupanc, Tomaž; Previderè, Carlo; Fattorini, Paolo
Highlights: A rectrospective study was conducted on the effect of the long term storage of DNA samples. Quantitative PCR (qPCR) was employed as tool for assessing the degradation of the samples. Forensic samples stored at – 20° in water for 0.1–10.2 years (groups #1-#5) and at +4 °C in water for 4.1 years (group #6) were selected. The median loss of DNA ranged from 17.8 % to 66.6 % in groups #1-#5 while it was 85.0 % in group #6. This study warns against the use of water for the long-term storage of DNA samples. Abstract: A rectrospective study was conducted on the effect of the long term storage of 122 DNA samples resuspended in water, one of the elution media still suggested by well established protocols. These DNA samples come from four different kinds of forensically relevant samples (saliva swabs, FTA card bloodstains, nails and II° World War bones) extracted in 2008–2018 and stored at – 20 °C (n = 113 of groups #1-#5) and at +4 °C (n = 9 of the group #6), respectively. At the time of the present study (2019), quantitative PCR (qPCR) was employed as tool for assessing the degradation of the samples. The employment of the Human Quantifiler Kit showed that the median loss of DNA ranged from 17.8% to 66.6% in groups #1-#5 while it was 85.0% in group #6. However, it is likely that these values represent an underestimation due to the shortness of the qPCR probe (62 bp). Noteworthy, the DNA loss was statistically significant in each of the six groups (p values ≤ 0.0167). Thus, in agreement with the data on spontaneous DNA decay, no forensic DNA sample should be stored in water for long term periods. In conclusion, the results of this technical note warn against the use of water for this purpose.